The utilization of concrete sludge of batching plant (CSBP) as a partial cement replacement in concrete - Muizzah Nawi, Nur; Asmani Mat Yusof, Doris; Shahidah Sharipudin, Siti; Farina Mohd Halim, Nora; Mayuze Mohamad, Nor; Zakuan Shafie, Mohammad (International Journal of Engineering and Technology, 2019)
Key players of construction industries prefer to use ready-mix concrete as one of the supplied materials for their projects. In conjunction with this, production of fresh concrete from batching plants is increasing consistently as the development of construction industries. Un-fortunately, more than 8 tons of fresh concrete waste can be obtained and return to the batching plants. In addition, most of the batching plants dispose the concrete waste on the ground or discharging them at the landfill. Thus, this research aims in correlating the strength response to the contribution of Concrete Sludge of Batching Plant (CSBP) as recycled materials and additives in the manufacturing of concrete. In this study, two different replacement levels in percentage of CSBP which are 10% and 20% to cement weight were adopted. The compressive strength of concrete specimens was performed in accordance with the BS EN 12390: 2009. The result revealed that the compressive strength of the CSBP concrete with 20% cement replacement is observed to gain the strength comparable than those of control sample by the value of 41.6 N/mm2 while the control sample achieved 42.6 N/mm2 at 28 days of age. It can be said that CSBP can be used as the potential of recycled material in the conventional concrete to support the green and sustainable approach in construction industries and to solve the issues of overloaded concrete sludge produce by batching plant.Â